Guselkumab in Inflammatory Bowel Disease: Mechanism, Clinical Efficacy, Safety, and Treatment Positioning - Laura White; Esha Sharma; Jimmy Limdi; Shahida Din; Kamal Patel; Sailish Honap (Journal of Clinical Medicine, 2026)
Guselkumab is a monoclonal antibody directed against the p19 subunit of interleukin-23 (IL-23), thereby preventing IL-23 binding to the IL-23 receptor. IL-23 is a key driver of immune dysregulation and chronic inflammation in inflammatory bowel disease (IBD), making selective IL-23 inhibition an established therapeutic strategy in both Crohn’s disease and ulcerative colitis. Guselkumab is the most recently approved IL-23p19 inhibitor for the treatment of both major forms of IBD. It is the first IL-23p19 inhibitor to offer a fully subcutaneous induction regimen, and preliminary phase III data has suggested potential benefits for patients with perianal Crohn’s disease. In registrational trials, there were significant improvements across multiple clinical and endoscopic endpoints in comparison to ustekinumab, although these trials were not powered for formal superiority testing. This narrative review summarises the biological rationale for IL-23 blockade, reviews the available clinical evidence, discusses practical considerations for its use, and considers its place in the landscape of IBD treatments.